Acid reflux episodes sensitize the esophagus to perception of weakly acidic and mixed reflux in non‐erosive reflux disease patients. Issue 1 (3rd October 2013) - Emerenziani, S.; Ribolsi, M.; Guarino, M. P. L.; Balestrieri, P.; Altomare, A.; Rescio, M. P.; Cicala, M.
Abstract Background Non‐erosive reflux disease (NERD) patients are more sensitive than erosive esophagitis patients to weakly acidic reflux and to the presence of gas in the refluxate. Intra‐esophageal acid perfusion sensitizes esophageal receptors to mechanical and chemical stimuli. Methods To establish whether acid sensitization plays a role in the perception of weakly acidic and mixed reflux episodes, 29 NERD patients, responders and 14 non‐responders to proton pump inhibitors (PPIs), underwent pH‐impedance monitoring. Non‐responders repeated the study while on PPIs. To assess the effect of acid exposure on symptom perception, the time period with pH below 4 was measured in 15‐ and 30‐minute time‐windows preceding the onset of each reflux episode. Key Results Considering weakly acidic and mixed refluxes, both in responder and non‐responder patients (off PPIs), the symptomatic refluxes were preceded by a significantly higher cumulative acid exposure than the asymptomatic refluxes. In all patients, following acid reflux, the percentage of symptomatic weakly acidic reflux episodes was significantly higher than that of asymptomatic refluxes. Non‐responder patients, off‐treatment, were characterized by a lower proportion of weakly acidic reflux and mixed reflux episodes. In the non‐responder patients on PPI, only mixed and weakly symptomatic reflux episodes were preceded by a higher cumulative acid exposure. Conclusions & Inferences In NERD patients, spontaneous acid reflux enhances subsequent reflux perception, regardless of acidity or liquid/mixed composition of episodes; in non‐responder patients on PPIs, only the perception of mixed and weakly acidic reflux episodes seems to be mediated by a preceding acid exposure.